OPTIMASI PENGELOLAAN SISTEM AGROFORESTRI CENGKEH, KAKAO DAN KAPULAGA DI PEGUNUNGAN MENOREH - ALAM, TAUFAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The problem of clove, cocoa and cardamom in Menoreh Mountain Area is low production due to diversity of topography. The improvement in production can be achieved by the management of ecological factor using physiological factor and crop production factor as well as social character of the people in Menoreh Mountain area. This Research, 'Optimization management of clove, cocoa, and cardamon agroforestry system in Menoreh Mountain Area' , was conducted in four phases. The first phase was to determine the level of land suitability towards the development of clove, cocoa and cardamom. The second phase was to find out the composition of vegetation on agroforestry system. The third phase was to know ecological factor that affected the physiological and crop yield of clove, cocoa and cardamom on agroforestry system. The fourth phase was to find out the society support in managing plants. This research was conducted in Menoreh Mountain Area, Samigaluh District, Kulonprogo Regency, The Province of Yogyakarta Special Territory from August, 2013 to February, 2014. The results showed that the actual and potential land suitability to clove in the lower, middle and top zone was respectively in N1m and S3wm, S3wrm and S3w, and N1m and S3wm. Cocoa was respectively in N1m and S3wm, S3wrm and S3w, and N1wm and N1w. Cardamom was respectively in N1m and S3m, S3rmn and S2wrm, and N1m and S3M. All zones have low to moderate plant diversity and abundance of low plant species. No interaction occurs between the altitude zones with the season on clove, cocoa and cardamom. The upper zone showed that the highest dry weight of clove was 3,48 ton.ha-1, while the lower and middle zones were respectively 0,95 ton.ha-1 and 3,08 ton.ha-1. Lower zone showed that the highest dry weight of cocoa beans was 104,47 kg.ha-1, while the middle and upper zones were respectively 19,61 kg.ha-1 and 5,03 kg.ha-1. The upper zone showed that the highest dry weight of cardamom pods was 0,805 ton.ha-1, while the lower and middle zones were respectively 0,154 ton.ha-1 and 0,202 ton.ha-1. Dry weight of cocoa beans in the dry season was 43,65 kg.ha-1 and not significantly different from the rainy season, which was 42,42 kg.ha-1. Dry weight of cardamom pods in the dry season was 0,381 ton.ha-1 and not significantly different from the rainy season, which was 0,394 ton.ha-1. Light absorption has the largest direct influence on the dry weight of clove. Ecological factors that influence the light absorption of clove were soil moisture content, the intensity of rainfall and run-off. Photosynthetic rate has the largest direct influence on the dry weight of cocoa beans and cardamom pods. Ecological factors that affect cocoa and cardamom photosynthesis rate are air temperature, potential evapotranspiration, and wind speed. Menoreh Mountain Area lower zone has moderate social factor support, while Menoreh Mountain in middle and upper zone has strong social support factor. Optimization management of ecological factor can be done by increasing the actual land suitability classes into potential. Optimization management of production factors of clove, cocoa and cardamom in terms of plant genetics can be done with the use of high-yielding varieties. In terms of environmental management and plant, It can be used by the plant room setting, fertilizer, and xxxii pest management. Optimization of society factors can be done by the improvement and enhancement of the role of public institutions and an increase in knowledge as well as farmer adoption levels of new conservation technologies .